Republic of Congo : Staff-Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Social and political stability has improved in Congo, but the security situation is fragile. Executive Directors welcomed the Staff-Monitored Program (SMP), which was designed to safeguard fiscal and external stability. They stressed the need for stabilizing the economy and pursuing structural reforms with a view for achieving sustainable growth, reducing poverty, diversifying the economy, and benefiting from enhanced HIPC Initiative debt relief. As a sign of their renewed commitment to reengagement with the IMF, authorities established a new organizational structure for better monitoring and implementation of the economic and financial program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet